Cardiac Device Infection due to Streptococcus pneumoniae - Theresa T Liu; Pablo B Nery; David Birnie; Peter Jessamine; Kathryn N Suh (Canadian Journal of Infectious Diseases and Medical Microbiology)
Cardiac device infections (CDIs) are recognized complications of device implantation. Most CDIs are caused by skin flora but can also result from hematogenous seeding of the device. A case involving Streptococcus pneumoniae CDI, which is rare, potentially vaccine preventable and may not be associated with overt antecedent pneumococcal infection, is reported.